Effect of psychographic characteristics on the intention to purchase private brands in Chile - Manzur M., Enrique; Hidalgo C., Pedro; Olavarrieta S., Sergio; Farías N., Pablo (Estudios de Administración, 2005)
Private Labels are steadily but slowly included in Chileans´ consumption baskets. However, they have not reached the market share and penetration levels of European countries. The mainobjective of this article is to study how customers` psychographics affect private labels buying intentions. A shopping center intercept study was conducted, interviewing 300 female shoppers, regarding 14 psychographic variables and private labels purchase intentions. Nine product categories were used, in order to improve the generalizability of findings. Using discriminant analysis, the relative importance of each psychographic variable to explain private labels´ purchasing intentions was assessed, in order to help retailers and manufacturers optimize their marketing efforts of private labels.